Chimeric H5 influenza virus-like particle vaccine elicits broader cross-clade antibody responses in chickens than in ducks - Park, Jaekeun; Song, Chang-Seon; Chung, David Hyunjung; Choi, Sangyong; Kwon, Junghoon; Youk, Sungsu; Lee, Dong-Hun (Frontiers in Veterinary Science, 2023)
Asian-lineage highly pathogenic avian influenza (HPAI) H5 viruses have spread throughout Asia, the Middle East, Europe, and Africa. These viruses are independently evolving into genetically and antigenically divergent clades, and broad-spectrum vaccines protecting against these divergent clades are needed. In this study, we developed a chimeric virus-like particle (VLP) vaccine co-expressing hemagglutinins from both clades 1 and 2.3.2.1 of HPAI H5 and performed comparative cross-clade hemagglutination inhibition (HI) analysis in chickens and ducks. The chimeric VLP immunization induced a significantly broader spectrum of antibodies against various clades of HPAI H5 viruses than monovalent VLPs both in chickens and ducks. While the chimeric VLP led to broadened antibody responses in both species, significantly lower levels of HI antibodies were elicited in ducks than in chickens. Moreover, boost immunization barely increased antibody responses in ducks regardless of VLPs used, in contrast to chickens that showed significantly enhanced antibody responses upon boost immunization. These results suggest 1) the potential application of the chimeric VLP technology to help control HPAI H5 viruses by offering broader antibody responses against antigenically different strains in poultry and 2) possible obstacles in controlling HPAI H5 viruses in ducks via vaccination, calling for advances in vaccination strategies that can effectively induce antibody responses to these viruses.